(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this study was to see the cardiometabolic risk among doctors using waist-to-height ratio index as tool. Cardiometabolic risk is an umbrella term that includes all the risk factors of diabetes and cardiovascular disease. The study was conducted among 195 doctors. According to waist-to-height ratio index 167 (85.6%) doctors had cardiometabolic risk. Waist-to-height ratio index was found good (area under the curve >0.5, sensitivity 88.1%, specificity 23.2%, positive predictive value 53.9%, and negative predictive value 66.7%) for their predictive value of cardiometabolic risk. Age grouping was done and found that no age group was free from cardiometabolic risk.